"Crises" as catalysts for more sustainable futures? The case of the first oil crisis and the role of multilayered interpretative struggles - Timur Ergen; Lisa Suckert (economic sociology_the european electronic newsletter, 2021)
"How dare you?" Greta Thunberg's exclamation in front of the UN was shaped by indignation but also disbelief. However, not only the young activists of Fridays for Future appear to be puzzled about humanity's difficulties in adequately responding to climate change. Ample scientific evidence for global warming and its causes is available, and potential policies for reducing CO2 emissions have long been developed, evaluated, and tested in practice. So why has the catastrophe on the horizon not induced substantial behavioral change? Why do we see so little reaction in the face of this all-encompassing crisis?
Keywords: 300